2019
DOI: 10.1111/jcpe.13113
|View full text |Cite
|
Sign up to set email alerts
|

Dental treatment procedures for periodontal disease and the subsequent risk of ischaemic stroke: A retrospective population‐based cohort study

Abstract: Aim To investigate the association between specific dental therapy for periodontal disease and the risk of ischaemic stroke. Materials and Methods We conducted a population‐based cohort study that used data from the Taiwan National Health Insurance Research Database 2005 for the period of 2000–2013. Our observations focused on patients with the diagnoses of gingivitis or periodontitis with and without specific treatment and subsequent incidence of ischaemic stroke. Dental care services include dental scaling, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 19 publications
1
27
1
3
Order By: Relevance
“…Several included studies did not adjust for smoking, a major modifiable risk factor for PD (Chou et al, 2015; DeStefano et al, 1993; Lee et al, 2017; Lee et al, 2015; Y. L. Lee et al, 2013; Lin et al, 2019). Smoking is also significantly associated with all CVD outcomes (Banks et al, 2019), in addition to increased periodontal tissue attachment loss and destruction of alveolar bone (Gautam et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Several included studies did not adjust for smoking, a major modifiable risk factor for PD (Chou et al, 2015; DeStefano et al, 1993; Lee et al, 2017; Lee et al, 2015; Y. L. Lee et al, 2013; Lin et al, 2019). Smoking is also significantly associated with all CVD outcomes (Banks et al, 2019), in addition to increased periodontal tissue attachment loss and destruction of alveolar bone (Gautam et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Another cohort study also revealed that participants with chronic periodontitis had an elevated risk for overall dementia (aHR = 1.06; 95% CI = 1.01-1.11) and AD (aHR = 1.05; 95% CI = 1.00-1.11) compared with those without periodontitis [10]. Moreover, a retrospective cohort study indicated that dental care services, including scaling and intensive treatment, reduced the risk of ischemic stroke in patients with periodontitis [11]. These observations are consistent with our findings, suggesting that periodontitis might be a risk factor for brain diseases.…”
Section: Discussionmentioning
confidence: 94%
“…Cohort studies reveal that patients with periodontitis exhibited a higher risk of developing AD [8] and dementia [9,10] than those without periodontitis. A retrospective cohort study reports that patients with periodontitis have a higher risk of ischemic stroke compared to those in the gingivitis cohort [11]. These observations indicate that periodontitis could be associated with brain diseases.…”
Section: Introductionmentioning
confidence: 98%
“…Due to the large number of possible risk factors for CVDs and periodontitis, although several potential confounders were adjusted for, it is possible that existing residual confounding factors were not excluded. For example, the periodontal treatment along with the study was shown to lower the risk of ischaemic stroke from the recent cohort (Lin et al, 2019). However, history of periodontal treatment was not considered in our study due to invalid self‐report data and lacking in detail and frequency of treatment.…”
Section: Discussionmentioning
confidence: 99%